The Effect of Personnel Participation and Work Motivation on Job Satisfaction in The New City Sector of The Karawang Police - Suherlan Suherlan; Kemal Taufik; Suhardi Suhardi (Dinasti International Journal of Management Science, 2026)
This study has the following objectives: To determine and analyze the effect of personnel participation on job satisfaction, to determine and analyze the effect of work motivation on job satisfaction, and to determine and analyze the joint effect of personnel participation and work motivation on job satisfaction, the calculated t value obtained is 2.075 while the t table value is 1.990 for N = 90, then 2.075 > 1.990, thus H0 is rejected and Ha is accepted, from this study it is proven that the participation variable (X1) has a positive influence on the job satisfaction variable (Y), the calculated t value obtained is 6.199 while the t table value is 1.990 for N = 90, then 6,199 > 1,990, thus H0 is rejected and Ha is accepted, from this study it is proven that the work motivation variable (X2) has a positive influence on the job satisfaction variable (Y). the calculated F value is 30.467 while the F table for N = 90 is 2.71. Thus the calculated F value (30.467) > F table (2.71), so clearly H0 is rejected and Ha is accepted. With F count > F table, it can be concluded that personnel participation (X1) and work motivation (X2) jointly have a positive influence on job satisfaction (Y).